Ensinando a lembrar: ensino de relatos de eventos passados a um paciente amnésico - Freitas, Dagliê Jorge de (2016)
The present study examined the effectiveness of social reinforcement in improving the accuracy and changing the topography of verbal self-reports about current behavior (“on-task self-report”) and past behavior (“immediate post-task self-report”) in an amnesiac outpatient. It also examined whether reinforcing accurate self-reports about current and previous behavior would result in generalization for self-reporting 30 s, 60s, 120 s and 240 s after the completion of a task. This study was conducted with a 45 year-old outpatient whose memory was impaired after suffering a cerebrovascular accident (CVA) thirteen years ago. The participant was instructed to carry out four different tasks (Reading, Assembling Lego, Looking for Shapes, Exercising) for every session (one per trial) and describe his behavior during and right after the completion of the task. After some probe sessions to determine the patient’s behavior of reporting about those four activities prior to the intervention in a multiple baseline design, a training session was introduced, in which praise was contingent to accurate self-reports about one of the four tasks. Later on, tests were undertaken to assess the acquisition and the maintenance of the trained self-reports and the effect of training on the other untrained tasks’ self-reports. There were training sessions for all tasks, except for Reading. Afterwards, tests were also undertaken in which instructions and the queries were manipulated in order to identify their effects on reporting. The results showed that, following training sessions, 1) there were fewer inaccurate immediate post-task reports; 2) the task Reading was no longer mentioned on on-task and immediate post-task reports; 3) self-edition no longer occurred; 4) the task Assembling Lego was mentioned for the first time on a inaccurate self-report; 5) for the task Exercising there were no more inaccurate on-task self-reports; 6) in post-tests following the training sessions of the reports of Looking for Shapes and Exercising, all inaccurate self-reports mentioned the task whose reports had just been trained. As for the participant’s performance after the Manipulation Tests, results indicated that 1) the topography of self-reports that mentioned one of the four tasks changed; 2) imprecise self-reports such as “I don’t know” and “I don’t remember” reemerged. In follow-up sessions, which took place 45 days after the experiment had finished, the participant emitted only correct post-task self-reports. Results indicated that, in spite of an unstable performance before and after the introduction of training sessions, social reinforcement as applied in the present study might have influenced the accuracy and the topography of verbal self-reports. Furthermore, results also indicated that both the instruction given at the beginning of every trial and the queries that requested self-reports controlled the accuracy and the topography of self-reports and that the presence of reinforcement during the tasks might render the occurrence of reports about those tasks more likely